2013
DOI: 10.5114/aoms.2013.39617
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review/Meta-analysis A systematic cost-effectiveness analysis of pregabalin in the management of fibromyalgia: an Iranian experience

Abstract: IntroductionFibromyalgia is a neuropathic syndrome which is more common in adult females. Pregabalin is the first medicine which was approved by the United States Food and Drug Administration for treatment of fibromyalgia. In this study we aimed to evaluate the cost-efficacy of pregabalin in the treatment of fibromyalgia in Iran.Material and methodsTo evaluate the efficacy of pregabalin, a systematic review was carried out by conducting a wide literature search for the main outcomes of interest that were pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Future interventional studies, i.e. generic treatments such as pregabalin [35] or specific interventions such as foot trigger points dry needling [36, 37] and custom-made foot orthotics [38] in women with fibromyalgia, could use these clinical differences as key references in order to normalize the specific foot and general health-related quality of life. In line with prior research [8], we highlight that health authorities should pay more attention to improving the general and foot specific health-related quality of life in women with fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Future interventional studies, i.e. generic treatments such as pregabalin [35] or specific interventions such as foot trigger points dry needling [36, 37] and custom-made foot orthotics [38] in women with fibromyalgia, could use these clinical differences as key references in order to normalize the specific foot and general health-related quality of life. In line with prior research [8], we highlight that health authorities should pay more attention to improving the general and foot specific health-related quality of life in women with fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, 58 , 59 the incremental cost-effectiveness ratios with pregabalin therapy was highest in patients with severe fibromyalgia and with 450 mg/day dosage. Studies from Iran 61 and Mexico 62 revealed consistent effects on cost saving, with most benefit with pregabalin 450 and 600 mg/day. 61 Comparative analyses of pregabalin and other drugs in fibromyalgia, especially duloxetine, have not always revealed consistent results with some studies pointing toward higher health care resource use with pregabalin, probably driven by more inpatient and outpatient visits and medication use, while others revealed nonsignificant difference between the two.…”
Section: Burden Of Fibromyalgiamentioning
confidence: 87%
“…Studies from Iran 61 and Mexico 62 revealed consistent effects on cost saving, with most benefit with pregabalin 450 and 600 mg/day. 61 Comparative analyses of pregabalin and other drugs in fibromyalgia, especially duloxetine, have not always revealed consistent results with some studies pointing toward higher health care resource use with pregabalin, probably driven by more inpatient and outpatient visits and medication use, while others revealed nonsignificant difference between the two. 63 Almost all cost-effectiveness analyses are dominated by amitriptyline because of its lower costs but the comparison between amitriptyline and pregabalin relies on older studies which may not meet current quality criteria 59 and the degree of overall clinical improvement (reduction of VAS score by >50% and decrease in FIQ score by 30%) is lower with amityrptyline.…”
Section: Burden Of Fibromyalgiamentioning
confidence: 87%
“…The first diagnostic criteria for fibromyalgia were published in 1990, defining chronic widespread pain with a number of tender points; however, newer classification criteria for fibromyalgia were proposed in 2010 [2][3][4][5]. Various drugs at different doses, such as amitriptyline, pregabalin, gabapentin, and duloxetine, are used in the treatment [6]. The aetiology of the disease is still not clearly understood.…”
Section: Introductionmentioning
confidence: 99%